Desenvolvimento de filmes de isolado proteico de soja incorporados de extrato da casca de pinhão (Araucaria angustifolia (Bertol.) Kuntze) e aplicação como embalagem para óleo - Souza, Karen Cristine de (2019)
Pinhão is a seed from Araucaria angustifolia, popularly known as Pinheiro do Paraná, which grows in southern Brazil, Argentina and Paraguay. Pinhão seeds are usually consumed cooked in water and peeled, and the coats are discarded as residue. Studies indicate that the pinhão coat presents antioxidant activity due to the presence of phenolic compounds. Thus, the pinhão coat extract is an excellent source of antioxidant that can be added in protein based biodegradable films, aiming to obtain active packaging. Based on this context, the present work aimed to develop films based on soy protein isolate (SPI) with the incorporation of different concentrations of pinhão coat extract (EP). In the films the mechanical properties, water vapor permeability (WVP), thermal properties, microstructure by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), antioxidant activity and total phenolic compounds concentration were determined. In the second phase of the work, the potential application of the films was investigated producing sachets with the control film (C) and with the film with 2% of EP (EP2) for storage of gold linseed oil. The incorporation of EP in the films did not significantly alter the mechanical properties and the WVP, but caused changes in the color of the films, giving a dark brown color. The films with EP presented significant antioxidant activity, correlating with the values of phenolic compounds. FTIR spectra revealed possible interactions between the EP and SPI and the differential scanning calorimetry (DSC) curves indicated an increase in the thermal stability of the films due to the EP addition. The stability of the linseed oil packed in the sachets was monitored by the peroxide index and the specific extinction coefficient (conjugated diene- K232, conjugated trienes -K270 and specific extinction variation-ΔK) of flaxseed oil were carried out during 10 days of accelerated storage (60ºC). After 10 days of storage, there was a positive effect of the EP2 film on the oxidative stability of linseed oil from the lower values of peroxide index, K232 and K270. Based on the results of this study, SPI films added with EP may be an interesting active biodegradable for foods rich in fat.